Politics and emotions the Obama phenomenon - Engelken-Jorge, Marcos; Ibarra Güell, Pedro; Moreno del Río, Carmelo (VS Verlag für Sozialwissenschaften, 2011)
Mainstream liberal narratives have often depicted politics as a matter of power and competing interests, disregarding emotions or conceiving them as threats to a rational and well-ordered society. In the last decades, however, this viewpoint has been increasingly challenged by a number of scholars researching on the complex and multidimensional role of emotions in politics. This edited collection aims at providing a concise but comprehensive introduction to this area of research. The essays contained in this volume focus on a single case, the Obama phenomenon, illustrating empirically how the variable ?emotions? can enrich political analysis. Taken together, the essays reflect the plurality of approaches available to the study of politics and emotions and thus contribute to the cutting-edge debates on this fascinating topic